A comparison of the early reading strategies of isiXhosa and Setswana first language learners - Tracy N. Probert (South African Journal of Childhood Education, 2019)
Background: A large amount of evidence highlights the obvious inequalities in literacy results of South African learners. Despite this, a sound understanding of how learners approach the task of reading in the African languages is lacking.